Evaluation of Practice and Awareness of the Safety Profile of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) among Dental Practitioners: A Cross-Sectional Study - A. F. Ben Saod , Loai; Ramadan Eid Albhbah , Wael (Scientific Journal of University of Benghazi, 2024)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the common medications used by dental practitioners to relieve dental pain and control post-operative signs of inflammation. NSAIDs, irrespective of their benefits, have a lot of hazards because of misuse and faulty prescriptions by dentists. The aim of this study is to evaluate the current use of NSAIDs during dental practice and to evaluate the association of the level of education and years of experience of dental practitioners with the awareness of the safety profile of NSAIDs. This observational cross-sectional study was conducted in Benghazi city between August and October 2024. The sample size is composed of 341 dentists. Participants were selected randomly from approximately every dental clinic in Benghazi. The questionnaire is composed of sections including assessment of drug use and drug-precautionary awareness. It is structured with checklist answers and was formulated in English. It is filled by the dentists during a visit to their dental clinics on the basis of an interview. The Statistics Package for Social Science Version 21 (SPSS) software was used for transferring and analysis of data. The results showed that the females accounted for the majority (60.7%). General practitioners represented 67.7% of the participants. About 61.0% of the dentists had clinical experience of less than 10 years. Ibuprofen and Ketoprofen were the most prescribed NSAIDs, 67.2% and 51.6, respectively. More than fifty percent (55.4%) of the participants used to prescribe NSAIDs for less than three days. Postoperative pain and dental pain were the most common clinical indications that NSAIDs were prescribed, 71.3% and 59.5%, respectively. Pregnancy was the most cited to be contraindicated (58.9%). Awareness of avoiding NSAIDs in the case of peptic ulcer patient was associated with years of experience of the dentists (P=0.030). Participants agreed that nausea was the most side effects (45.2%). Awareness of the interaction between NSAIDs and warfarin was associated with the level of education (P=0.006). The outcomes of the study have revealed less comprehension regarding scientific background knowledge of NSAIDs. There was little effect of level of education and years of experience on the awareness of the safety profile of NSAIDs during dental practice. Therefore, a lot of efforts should be focused on improving the knowledge for making proper therapeutic decisions and minimizing the risk of serious adverse effects on the patients who attend dental clinics.